Study and analysis of the story “The Happy Prince” by Oscar Wilde - Méndez-Vega, Mauricio (2023)
This article begins with a general introduction and then with a detailed explanation about the concept of the artistic movement called estheticism. Besides, the main representative authors are cited. Throughout the article, there is a biographic presentation of the Irish writer Oscar Wilde and there is a detailed study and analysis, according to the bibliographic sources and literary and technical concepts about his short story “The Happy Prince”